Contact resistance, coupling and hysteresis loss measurements of ITER poloidal field joint in parallel applied magnetic field. (7th January 2022) - Huang, J; Ilyin, Y; Wessel, W A J; Lubkemann, R; Krooshoop, H J G; Nijhuis, A
Abstract: The inter-strand contact resistance and AC losses were measured on an International Thermonuclear Experimental Reactor (ITER) poloidal field (PF) coil joint in a parallel applied AC magnetic field. In addition, the hysteresis loss was measured as a function of the angle with the applied magnetic field on a niobium-titanium (NbTi) strand of the same type as in the joint with a vibrating sample magnetometer. The AC loss measurements were performed at four applied field conditions for combinations of 0 or 1 T offset field and 0.2 or 0.4 T sinusoidal amplitude. The hysteresis loss of the joint was compared with the measured AC loss density of the NbTi strand for the same field conditions as the joint AC loss measurement but with varying the angle of the applied field. The subsequent cable twist angles affect the hysteresis loss since the critical current and penetration field depend on the angle of the applied field. It is found that 15.5° is an effective angle for the calculation of the hysteresis loss of joint when compared to the single strand measurement. The inter-strand contact resistance measurements cover all the typical strand combinations from the five cabling stages of the individual conductors, as well as the strand combinations across the two conductors to characterize the inter-strand including the copper sole resistivity. It is the first time to measure the contact resistances and AC losses of the full-size ITER PF joint. By comparing the measured and simulated data in the JackPot-ACDC model, it is also the first time to obtain the accurate inter-strand, inter-petal and strand to copper sole contact resistivities, which are the main input parameters for the further quantitative numerical analysis of the PF joints, in any current and magnetic field conditions.